Un processus d’enquête à l’université par la narration professionnelle - Simon Mallard (Éducation et Socialisation)
This article explores the first training experience of teachers entering the career in professional and technological sectors. The author analyses what is involved in a pedagogical action by examining educational or teaching situations in what he calls collaborative investigation. According to him, using the concept of device makes it possible to understand the operation and principles of the action. The article also promotes the description and the analysis of both convergences and tensions between the actors’ initiatives in the system (designers, trainers, and teachers in training device).Narrative work appears prominent in this system by promoting dialogue around the profession of teacher in a professional and technological High School. In such case, the logic of inquiry supports the process of exchange between trainees and a kind of collective storytelling. This approach encourages confrontation with the professional gender of the teaching profession and also the positioning, but also emergence, of a style-action.